The Abusive Mother-Daughter Relationship in The Act the Series (2019) - Merry Indah Santosa; Setefanus Suprajitno (Kata Kita: Journal of Language, Literature, and Teaching, 2025)
In this article, we analyze the abusive mother-daughter relationship in The Act (2019). The Act (2019) is a true crime drama series based on the real-life story of Gypsy Rose Blanchard and her mother, Dee Dee Blanchard. The series tells the journey of Dee Dee’s physical and mental abuse, as well as her controlling behaviour toward Gypsy. In this analysis we focus on how Dee Dee treats Gypsy and why Gypsy responds to Dee Dee’s treatment in certain ways. We will use Nussbaum’s objectification theory to analyze Dee Dee’s treatment, and McClelland’s three social motive theory to explain Gypsy’s responses. The findings reveal that Dee Dee has the desire for power, recognition and wealth, while Gypsy has the need for independence and affiliation pushes her towards rebellious actions. This study concludes that a mother figure does have an impact on a child’s growth and development.